2005
DOI: 10.1016/j.mambio.2004.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity within Anatolian brown hares (Lepus europaeus Pallas, 1778) and differentiation among Anatolian and European populations

Abstract: Genetic variability of Anatolian hares and relationships between Anatolian and European populations were assessed by a multilocus allozyme approach to infer evolutionary relationships between hares from Asia Minor and Europe. Of the 48 loci assayed, 19 (39.6%) were polymorphic with two to four alleles in the Anatolian hares. Among all Anatolian alleles, 14 were so far not found in the compared 717 brown hares from Europe. Overall, genetic diversity was highest in Anatolian hares, intermediate in brown hares fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
55
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 30 publications
8
55
0
3
Order By: Relevance
“…The findings of the present study regarding the pelage color were in line with those of Yom-Tov (1967). Sert et al (2005) reported that genetic diversity was the highest in Anatolian hares, moderate in brown hares from the southern and southeastern Balkans, and the lowest in Central European populations. However, Sert et al (2005) stated that genetic differentiation among Anatolian populations was low and there was an increase in genetic diversity only among some population pairs that were distributed distantly from each other.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The findings of the present study regarding the pelage color were in line with those of Yom-Tov (1967). Sert et al (2005) reported that genetic diversity was the highest in Anatolian hares, moderate in brown hares from the southern and southeastern Balkans, and the lowest in Central European populations. However, Sert et al (2005) stated that genetic differentiation among Anatolian populations was low and there was an increase in genetic diversity only among some population pairs that were distributed distantly from each other.…”
Section: Discussionsupporting
confidence: 89%
“…However, according to Sert et al (2005), this distinct color difference was not in parallel with a pronounced genetic diversity. Sert et al (2005) also reported that even though many alleles found in Anatolian hares were not found in European populations, their allozyme data indicated a close phylogenetic relationship between European and all Anatolian brown hares. Sert (2006) recorded that the variations of the fur color occurred by means of the narrowing and expansion of light and dark bands or the disappearance of some bands of hairs.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations